2019
DOI: 10.1016/j.agee.2019.106575
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of enteric methane production, yield and intensity of beef cattle using an intercontinental database

Abstract: Enteric methane (CH 4 ) production attributable to beef cattle contributes to global greenhouse gas emissions. Reliably estimating this contribution requires extensive CH 4 emission data from beef cattle under different management conditions worldwide. The objectives were to: 1) predict CH 4 production (g d −1 animal −1 ), yield [g (kg dry matter intake; DMI)−1 ] and intensity [g (kg average daily gain) −1 ] using an intercontinental database (data from Europe, North America, Brazil, Australia and South Kore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 60 publications
(99 reference statements)
12
34
1
Order By: Relevance
“…The average yield of 15.2 ± 4.2 g of CH 4 /kg of DMI for diets low in forage (<18% forage) reported by these authors is similar to the CH 4 yields reported in Table 2. Similarly, the CH 4 yield factor from Experiment 2 ( Table 3) is similar to the 20.7 ± 4.7 g of CH 4 /kg of DMI reported by van Lingen et al [7] for beef cattle diets with more than 25% forage. The lower CH 4 yield observed in Experiment 1 for the CC and CB treatments in comparison with the CO treatment and the low total daily emissions observed in Experiment 2 suggest that these herbs reduced enteric CH 4 emissions in terms of CH 4 yield and daily emission in g/d, respectively.…”
Section: Methane Productionsupporting
confidence: 86%
See 3 more Smart Citations
“…The average yield of 15.2 ± 4.2 g of CH 4 /kg of DMI for diets low in forage (<18% forage) reported by these authors is similar to the CH 4 yields reported in Table 2. Similarly, the CH 4 yield factor from Experiment 2 ( Table 3) is similar to the 20.7 ± 4.7 g of CH 4 /kg of DMI reported by van Lingen et al [7] for beef cattle diets with more than 25% forage. The lower CH 4 yield observed in Experiment 1 for the CC and CB treatments in comparison with the CO treatment and the low total daily emissions observed in Experiment 2 suggest that these herbs reduced enteric CH 4 emissions in terms of CH 4 yield and daily emission in g/d, respectively.…”
Section: Methane Productionsupporting
confidence: 86%
“…The CH 4 yield values obtained with the CO diet in Experiment 1 were similar to those reported in the literature, for example, van Lingen et al [7] developed an intercontinental enteric CH 4 production database with 1021 individual animal records from beef cattle and calculated important variables such as the average daily emissions (g/d/animal) and CH 4 yield (g of CH 4 /kg of DMI). The average yield of 15.2 ± 4.2 g of CH 4 /kg of DMI for diets low in forage (<18% forage) reported by these authors is similar to the CH 4 yields reported in Table 2.…”
Section: Methane Productionsupporting
confidence: 78%
See 2 more Smart Citations
“…In ruminants, DMI and gross energy intake (GEI) are considered to be the predominant drivers of enteric methane production [33]. A meta-analysis of an international beef cattle database, used to determine a prediction equation for inventory purposes, actually showed that DMI was the most important predictor of CH 4 [34]. The studies used in this meta-analysis covered a wide range of regions, systems or diets and showed a large variability of CH 4 and DMI records: DMI = 8.13 ± 2.82 kg/d and CH 4 = 161 ± 70.5 kg/d, much larger than the individual variability observed in the current study.…”
Section: Recorded Traitsmentioning
confidence: 99%